2003
DOI: 10.1046/j.0305-1846.2003.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐16 expression in lymphocytes and microglia in HIV‐1 encephalitis

Abstract: IL-16 is a natural ligand for the CD4 molecule and is known for its chemotactic and anti-HIV-1 activities. We determined IL-16 expression in human brain tissue with HIV-1 encephalitis by specific immunocytochemistry and showed that infiltrating lymphocytes and activated microglia express IL-16. IL-16 immunoreactivity was particularly pronounced in microglial nodules. In vitro, human foetal microglia and not astrocytes produce IL-16, and HIV-1 infection up-regulates microglial IL-16 release in a Nef-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…However, infiltrating lymphocytes and activated microglia in brains with HIV-1 encephalitis might show strong immunoreactivity for IL-16, a natural ligand of CD4. Because this cytokine inhibits HIV-1 propagation, lymphocytes might contribute to an innate antiviral immune response in the CNS in addition to microglia (Zhao et al, 2004). Furthermore, IL-4 and interferon (IFN)-g, two cytokines with important roles in immune regulation, are produced by different lymphocyte populations and seem to induce in microglia a cytoprotective phenotype (Butovsky et al, 2005).…”
Section: From Neuropathology Of Hiv Infection To Development Of Mcmd/hadmentioning
confidence: 98%
“…However, infiltrating lymphocytes and activated microglia in brains with HIV-1 encephalitis might show strong immunoreactivity for IL-16, a natural ligand of CD4. Because this cytokine inhibits HIV-1 propagation, lymphocytes might contribute to an innate antiviral immune response in the CNS in addition to microglia (Zhao et al, 2004). Furthermore, IL-4 and interferon (IFN)-g, two cytokines with important roles in immune regulation, are produced by different lymphocyte populations and seem to induce in microglia a cytoprotective phenotype (Butovsky et al, 2005).…”
Section: From Neuropathology Of Hiv Infection To Development Of Mcmd/hadmentioning
confidence: 98%
“…However, infiltrating lymphocytes and activated microglia in brains with HIV-1 encephalitis might show strong immunoreactivity for IL-16, a natural ligand of CD4 that inhibits HIV-1 propagation. Thus, lymphocytes might contribute to an innate antiviral immune response in the CNS in addition to microglia [137]. Furthermore, different lymphocyte populations produce IL-4 and interferon (IFN)-, two cytokines with important roles in immune regulation that seem to induce in microglia a cytoprotective phenotype [15].…”
Section: Neuropathology Of Hiv Infection and Development Of Hadmentioning
confidence: 99%
“…Since this cytokine inhibits HIV-1 propagation, lymphocytes might contribute to an innate antiviral immune response in the CNS in addition to microglia. 37 Cell migration also engages adhesion molecules, and increased expression of vascular cell adhesion molecule-1 (VCAM-1) has been implicated in mononuclear cell migration into the brain during HIV and SIV infection. 30,31,38 As an alternative to entry via infected macrophages, it has been suggested that the inflammatory cytokine, tumor necrosis factor-alpha (TNF-a), promotes a paracellular route for HIV-1 across the BBB.…”
Section: From Hiv Entry Into the Brain To Development Of Mcmd/hadmentioning
confidence: 99%
“…Therapeutic concentrations of VPA (0.6 mM) resulted in (1) significant increases in both nuclear and cytoplasmic bcatenin protein levels; (2) decreases in the level of protein akinase C and epsilon isozymes 182 and (3) downregulation of myristoylated alanine-rich C-kinase substrate (MARCKS) 183 through inositol-independent mechanisms. 184 VPA-mediated neuroprotection involves diminished activity of GSK-3b via the inhibition of phosphorylation of b-catenin (Ser 33,37 ) and tau (Ser 202 and Thr 181 ), 185 as well as the overall increase in total b-catenin protein levels (Figure 3). Hyperphosphorylation of b-Catenin and tau directly affects neuronal apoptosis and dysfunction.…”
mentioning
confidence: 99%